Validity and Reliability of New Three-Dimensional Reference Systems for Soft Tissue Analysis Using Non-Ionizing Three-Dimensional Imaging - Rongo, Roberto; D’Antò, Vincenzo; Michelotti, Ambrosina; Cornelis, Marie A.; Cattaneo, Paolo M. (Applied sciences, 2024)
Background: The aim of this study was to evaluate the accuracy and the repeatability of two reference systems for three-dimensional facial scans (FSs) compared with a reference system based on cone-beam computed tomography (CBCT). Subjects and methods: A total of sixty subjects, thirty growing participants (8–17 years old) and thirty non-growing participants (older than 21 years old), with FSs and full-field-of-view CBCT were included. Two different reference systems on the same FS were constructed. To assess validity, the two reference systems based on FSs were compared with the reference systems built using the CBCT scans. After two weeks, all of the FSs were reassessed to evaluate intra-operator repeatability. Reliability and repeatability were evaluated by means of parametric and non-parametric tests, intra-class correlation, the Dahlberg formula, and Bland–Altman plots (p < 0.05). Results: Both reference systems presented good reliability and showed a small difference with respect to the CBCT-based sagittal plane (Sagittal FS1 = 1.90 ± 0.98°; Sagittal FS2 = 1.80 ± 1.13°; p = 0.232). Between them, the two reference systems showed a small difference in the position of the sagittal plane (Sagittal FS1^Sagittal FS2 = 1.39 ± 1.13°). Conclusions: Both reference systems assessed in this study showed good intra-operator repeatability and their use may be suggested as reliable reference systems for FSs.